A silicon nitride ceramic substrate and its preparation method and application

By rationally preparing and adopting casting composite constant strong magnetic field molding technology in inorganic powders, the problems of low thermal conductivity, low strength and toughness, and uneven color of the silicon nitride ceramic substrate are solved, and a high-performance silicon nitride ceramic substrate is achieved.

CN117185825BActive Publication Date: 2025-04-25CHONGQING RES INST OF HARBIN UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311071130.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-04-25
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

The existing silicon nitride ceramic substrates have problems such as low thermal conductivity, low strength and toughness, and uneven color.

Method used

By reasonably preparing α-Si3N4, β-Si3N4 whiskers, single-crystal nanodiamonds, sintering aids and composite colorants in inorganic powders, casting composite constant strong magnetic field molding technology is used to form a high-performance silicon nitride ceramic substrate.

Benefits of technology

A silicon nitride ceramic substrate with high thermal conductivity, high strength, high toughness and uniform color has been achieved, which has improved the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117185825B_ABST
    Figure CN117185825B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of silicon nitride ceramic materials, and specifically relates to a silicon nitride ceramic substrate and a preparation method and application thereof. The present invention provides a silicon nitride ceramic substrate with high thermal conductivity, high strength, high toughness and uniform color by matching various raw materials in inorganic powder and adjusting the dosage. 3 N 4 As the main phase material, doped with β-Si with a fixed aspect ratio 3 N 4 The fiber is the first auxiliary phase material, the single crystal nano diamond is the second auxiliary phase material, and the sintering aid xRE is added 2 O 3 ‑(1‑x)MgAl 2 O 4 , composite colorant aFe 2 O 3 ‑bCr 2 O 3 ‑cEr 2 O 3 ‑dWO 3 , using texturing molding technology and gas pressure sintering process, high-performance, high-reliability and high-stability silicon nitride ceramic substrates have been prepared, which will help promote the industrialization of silicon nitride ceramic substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicon nitride ceramic materials, and in particular relates to a silicon nitride ceramic substrate and a preparation method and application thereof. Background Art

[0002] Insulated gate bipolar transistor (IGBT) is a composite fully controlled voltage-driven power semiconductor device composed of a bipolar junction transistor (BJT) and an insulated gate field effect transistor (MOSFET). It has excellent performances such as high frequency, high voltage, high current, and easy switching. It is the core control device of high-power converters and is widely used in rail transportation, smart grid, aerospace, electric vehicles, and new energy equipment. Driven by the vigorous development of new energy devices, 5G base stations, and the electric vehicle industry, the demand for IGBTs will have an explosive growth trend in the future. The expansion of the IGBT market will inevitably drive the supply demand for upstream key raw materials. The core packaging material of IGBT modules - ceramic substrates, has a bright future. Ceramic substrates are widely used in various types of high-reliability packaging due to their good airtightness and stable chemical properties. Among them, silicon nitride ceramic substrates have excellent thermal conductivity, mechanical strength, and reliability, and are the best high-frequency and high-power IGBT module packaging substrate materials with comprehensive performance.

[0003] Silicon nitride is a strong covalent bond compound with no melting point. It sublimates and decomposes directly into gaseous Si and N2 at about 1860℃. With the help of molecular dynamics methods, Hiroshi et al. calculated the theoretical thermal conductivity of α-Si3N4 and β-Si3N4 single crystals. The two have different high thermal conductivities: the theoretical thermal conductivity of α-Si3N4 single crystal is 105W / (m·K) along the a-axis and 225W / (m·K) along the c-axis; the theoretical thermal conductivity of β-Si3N4 single crystal is 170W / (m·K) along the a-axis and 450W / (m·K) along the c-axis. Unfortunately, there is a big gap between the actual thermal conductivity of Si3N4 ceramics and the theoretical thermal conductivity. The thermal conductivity of silicon nitride substrates currently used in commercial applications is 60-90W / (m·K) and the bending strength is about 650MPa. The main reasons for the influencing factors are: lattice arrangement, lattice oxygen content, phase composition, grain boundary phase content, ceramic pores, density and other impurity defects. Therefore, people have carried out a lot of research on improving thermal conductivity, strength and toughness in terms of raw material powder, sintering aids, molding methods, sintering methods, etc.

[0004] In addition, the color uniformity of silicon nitride ceramic substrates after sintering is another problem faced in the actual production process. Compared with hot pressing and hot isostatic pressing, the biggest advantage of gas pressure sintering is that it can prepare products with better performance and complex shapes at a lower cost and realize mass production. It is the most widely used process for manufacturing high-performance silicon nitride ceramics. However, due to the interaction between additives, impurities, sintering atmosphere and silicon nitride, as well as the influence of parameters such as gas pressure, sintering temperature and time, the sintered silicon nitride ceramics usually show uneven gray coloring in the near-surface area and gray coloring characteristics of the bulk material. This is because free Si is inevitably generated during the sintering process of silicon nitride, producing metal silicide impurities with a size range from a few nanometers to a few microns and acting as color centers, which will cause uneven coloring inside the material, and the decolorization process that occurs during the high-pressure step of heat preservation sintering and during the cooling period after the end of the high-temperature heat preservation stage of sintering will cause uneven surface coloring. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of low thermal conductivity, low strength and toughness, uneven color, etc. of the silicon nitride ceramic substrate in the prior art, thereby providing a silicon nitride ceramic substrate and a preparation method and application thereof.

[0006] To this end, the present invention provides the following technical solutions:

[0007] The present invention provides a silicon nitride ceramic substrate, which is prepared from an inorganic powder and includes the following components in percentage by mass based on the total mass of the inorganic powder:

[0008] α-Si3N4 accounts for 91% to 94%;

[0009] β-Si3N4 whiskers account for 2% to 4%;

[0010] Single crystal nanodiamond accounts for 1% to 2%;

[0011] The proportion of sintering aids is 2.5% to 4.5%;

[0012] The proportion of composite colorants is 0.5% to 0.8%;

[0013] The composition of the composite colorant is aFe2O3-bCr2O3-cEr2O3-dWO3, and a:b:c:d=(0.04-0.06):(0.03-0.05):(0.1-0.2):(0.69-0.83).

[0014] Optionally, the sintering aid is composed of xRE2O3-(1-x)MgAl2O4, wherein 0.7≤x≤0.9, and RE is a lanthanide rare earth element;

[0015] Optionally, RE includes at least one of the elements La, Ce, Nd, Gd, and Yb.

[0016] Optionally, the silicon nitride ceramic substrate satisfies at least one of the following (1)-(5):

[0017] (1) α-Si3N4 purity>95wt%, particle size distribution D50 is 0.6~0.8μm, specific surface area SSA is 10~13m 2 / g, O content ≤ 0.8wt%, metal impurity content Al < 100ppm, Fe < 100ppm;

[0018] (2) The length of β-Si3N4 whiskers is 2 to 3 μm, the diameter is 0.3 to 0.4 μm, and the aspect ratio is 6 to 12;

[0019] (3) Single crystal nanodiamond is spherical or quasi-spherical, with a purity of >99.9%, a particle size distribution D50 of 40-50 nm, and a specific surface area SSA of 260-300 m 2 / g;

[0020] (4) The purity of sintering aid is >99.99%, and the particle size distribution D50 is 0.2-0.4 μm;

[0021] (5) The purity of the composite colorant is >99.99%, and the particle size distribution D50 is 0.2-0.4 μm.

[0022] The present invention also provides a method for preparing the above-mentioned silicon nitride ceramic substrate, comprising the following steps:

[0023] S1, preparing inorganic powder into casting slurry;

[0024] S2, casting the obtained casting slurry in the presence of a magnetic field to obtain a casting green body, wherein the direction of the magnetic field is perpendicular to the casting direction;

[0025] S3, debinding and sintering the obtained tape-cast green body to obtain the silicon nitride ceramic substrate.

[0026] Optionally, in step S2, the magnetic field strength is 2T to 4T.

[0027] Optionally, in step S1, the casting slurry further includes a dispersant, a binder and a plasticizer;

[0028] And / or, the viscosity of the casting slurry is 15000-20000 mPa·s.

[0029] Optionally, in step S2, during the tape casting process, the scraper height is set to 0.5-0.8 mm, the tape casting speed is set to 0.15-0.25 m / min, the drying temperature is set to 30-90° C., and the green body thickness is set to 0.2-0.4 mm;

[0030] And / or, the diameter of the green body is Φ120-180 mm.

[0031] Optionally, in step S3, the debinding step includes heating the tape-cast green body to 250-270°C at a rate of 0.5-0.8°C / min under a protective atmosphere, and keeping the temperature for 4-8 hours; then heating the green body to 320-350°C at a rate of 1-2°C / min, and keeping the temperature for 4-8 hours; then heating the green body to 580-620°C at a rate of 2-3°C / min, and keeping the temperature for 6-8 hours.

[0032] Optionally, in step S3, the sintering step includes heating to 1400-1500°C at 8-12°C / min under a N2 pressure of 0.1-0.3MPa, and keeping warm for 1-2h; then pressurizing to a N2 pressure of 2-3MPa, heating to 1850-1900°C at 4-6°C / min, and keeping warm for 6-12h.

[0033] In the present invention, the operation of step S3 can be to place the tape-cast green body into a boron nitride or graphite crucible, and use a uniform mixed powder of Si3N4:BN:C=(35~45)wt%:(35~45)wt%:(10~30)wt% to spray and cover the green body, stacking 6 to 8 layers; then perform the subsequent debinding and sintering steps.

[0034] Lamination and mixed powder spraying are relatively common operations in the field. The purpose of lamination is to increase the number of green sheets placed in each crucible, thereby increasing the effective output of ceramic substrates. Mixed powder spraying covers the surface of the green sheets, so that there is a thin layer of micro powder between the two green sheets of the laminate to separate them, in order to prevent the laminated ceramic substrates from sticking together and being unable to be separated after sintering.

[0035] However, the raw material composition and ratio selection of the mixed powder in the present invention are different from the prior art. This application adopts the Si3N4-BN-C material system, and its main functions are: 1) effectively inhibiting the decomposition of Si3N4 at high temperature; 2) BN and Si3N4 do not react at high temperature, so that the mixed powder and the sample do not produce contact; 3) the introduction of carbon can eliminate the oxide impurity SiO2 on the surface of Si3N4 powder, effectively reduce the lattice oxygen content of Si3N4 ceramics and increase the N / O atomic ratio of the second phase between crystals, thereby helping to improve its thermal conductivity.

[0036] The present invention also provides an application of the silicon nitride ceramic substrate or the silicon nitride ceramic substrate prepared by the above preparation method in the field of electronic packaging.

[0037] In the present invention, the reasons for selecting some raw materials in the inorganic powder are as follows:

[0038] β-Si3N4 whiskers: During the high-temperature sintering of silicon nitride ceramics, the raw material low-temperature phase α-Si3N4 will be transformed into the high-temperature phase β-Si3N4 through the dissolution-precipitation mechanism, but the crystal transformation is not complete during the sintering process, and the untransformed α-Si3N4 will greatly affect the thermal conductivity of silicon nitride ceramics. After adding a certain amount of β-Si3N4 whiskers to the silicon nitride raw material, the driving force for the growth of β-Si3N4 grains can be increased, which is conducive to grain growth, reducing defects such as lattice oxygen, and is conducive to the improvement of thermal conductivity. The α→β phase transformation is a process in which equiaxed α-Si3N4 particles dissolve in the liquid phase and then precipitate long columnar β-Si3N4 grains, and the shape of Si3N4 grains has changed. This long columnar β-Si3N4 grain will produce crack deflection, crack bridging and grain pull-out effects, increase crack propagation resistance, and thus significantly improve the fracture toughness of Si3N4 materials, while also improving the strength of the material. The presence of high aspect ratio β-Si3N4 grains can further improve the strength and toughness of the material, and the material has an R-curve fracture behavior. The aspect ratio of β-Si3N4 grains varies not only with the initial powder properties and specific sintering process parameters, but also with the grain boundary glass phase composition, viscosity and volume, and the solubility of nitrogen.

[0039] Single-crystal nanodiamond: Introducing single-crystal nanodiamond as the second auxiliary phase material into silicon nitride material, on the one hand, because of its high surface activity and low Debye temperature (that is, the interatomic bonding force of nanodiamond is small and it has great activity), it helps to improve the sintering activity of silicon nitride ceramics and increase the driving force during the sintering process; on the other hand, because of its high thermal conductivity, it can effectively improve the thermal conductivity of silicon nitride ceramics.

[0040] Sintering aids: It is difficult to densify silicon nitride ceramics through material transfer processes such as diffusion. Therefore, it is necessary to add sintering aids to the material system to form liquid phase materials at high temperature. After particle rearrangement, dissolution diffusion-precipitation and closed pore elimination processes, the densification of silicon nitride ceramics can be achieved. Silicon nitride ceramic sintering additives are mainly divided into two categories: metal oxides and rare earth oxides. These oxides react with the SiO2 oxide film on the surface of Si3N4 particles to form a low eutectic silicate or M-Si-ON (M is a metal ion or atom) liquid phase at a lower temperature. The liquid phase wets the α-Si3N4 particles and fills between the particles. The particles are rearranged by the action of surface tension. At this time, the green body shrinks, the density increases, and the porosity decreases. As the temperature increases, the viscosity of the liquid phase decreases, and the α-Si3N4 particles dissolve in the liquid phase. When the supersaturated concentration is reached, long columnar β-Si3N4 particle grains are precipitated, that is, the α→β phase transition of the dissolution-precipitation process occurs. During the cooling process, the M-Si-ON liquid phase is retained as amorphous glass and becomes a grain boundary glass phase. These glass phases are combined with β-Si3N4 grains, and the β needle-shaped grains grow to form an interwoven structure, which gives the material high strength and fracture toughness.

[0041] Composite colorant: Fe2O3-Cr2O3-Er2O3-WO3 is an inorganic oxide system, and the coloring mechanism is a mixed coloring principle of crystal coloring and ion coloring. Its coloring power, hiding power, dispersion and stability are relatively reliable. On the one hand, it can not decompose and discolor at the firing temperature of silicon nitride ceramics, and it does not volatilize and escape, and has high heat resistance and high temperature stability; on the other hand, it can resist the corrosion of sintering aid melt and chemical stability. aFe2O3-bCr2O3-cEr2O3-dWO3 composite colorant is a uniform powder after pre-sintering at 1200-1400℃ and fine grinding.

[0042] The present invention has no special requirements for the specific preparation steps of the tape casting slurry, as long as the final viscosity range is controlled to be moderate. The selection and dosage of the solvent and auxiliary agent in the tape casting slurry are conventional in the field, for example, a binary azeotropic mixture of anhydrous ethanol and acetone is selected as a solvent (anhydrous ethanol: acetone = 68%: 32%), accounting for 80-100% of the total weight of the inorganic powder; triolein is used as a dispersant, accounting for 3-5% of the total weight of the inorganic powder; polyvinyl butyral is used as a binder, accounting for 15-20% of the total weight of the inorganic powder; butyl benzyl phthalate is used as a Class I plasticizer, which is used to soften the binder polymer chain and change the Tg of the binder, accounting for 6-8% of the total weight of the inorganic powder; polyethylene glycol is used as a Class II plasticizer, which acts as a lubricant in the tape casting blank to prevent the cross-linking reaction between the polymer long chains, accounting for 2-4% of the total weight of the inorganic powder. Specifically, the preparation steps of the tape casting slurry in the present invention can be: after weighing the composite colorant and the solvent (ethanol / acetone azeotrope) in proportion, add them into a nylon lined vacuum ball mill, the ball milling medium is silicon nitride grinding balls, a planetary ball mill is used, the speed is 300-350r / min, and the first ball milling is performed for 4-6h; then α-Si3N4 powder, β-Si3N4 whiskers, sintering aid, dispersant (triolein, phosphate ester or fish oil, etc.) The solvent is weighed by specific gravity and added to the ball mill in turn, the speed is 300-350r / min, and the second ball milling is carried out for 12-16h; finally, the adhesive (polyvinyl butyral or ethyl methacrylate, etc.) and the plasticizer (including Class I plasticizer butyl benzyl phthalate or dibutyl phthalate and Class II plasticizer polyethylene glycol or polyalkylene glycol, etc.) are added in turn, the speed is 300-350r / min, and the third ball milling is carried out for 20-24h. The ball-milled slurry is vacuum degassed at a vacuum degree of 10Kpa for 0.5-2h to obtain a silicon nitride tape casting slurry with a viscosity of 15000-20000mPa·s.

[0043] In the preparation process of the present invention, a magnetic field is applied during the tape casting process because during the solidification of the slurry, these diamagnetic ceramic grains will be oriented under the action of a strong magnetic field, and then textured ceramics can be obtained by sintering outside the magnetic field. The grain orientation is carried out in a liquid medium, so the grains will be affected by the viscous force generated by the liquid medium during the rotational orientation process. When diamagnetic ceramic grains with magnetic anisotropy are subjected to a strong magnetic field, they will generate anisotropic magnetization energy.

[0044] Since silicon nitride crystals are anti-magnetic, the a-axis or b-axis magnetic susceptibility is greater than the c-axis magnetic susceptibility. When formed in a longitudinal magnetic field, the a-axis or b-axis magnetization energy is less than the c-axis magnetization energy. Then the c-axis is arranged in the plane along the tape-casting direction, and the a-axis or b-axis of the crystal will be arranged along the direction of the magnetic field, obtaining a-axis or b-axis oriented silicon nitride ceramics.

[0045] Silicon nitride ceramics are anisotropic, and the arrangement of Si3N4 grains is also oriented. The thermal conductivity in different directions is also different, and it has higher thermal conductivity in specific directions. Therefore, by controlling the orientation of the grains, the directional growth of ceramic grains is achieved, and the microstructure of silicon nitride ceramics can be controlled without being affected by elements such as grain size, morphology and material type to obtain excellent performance.

[0046] For ceramic particles with antimagnetic properties, it is possible to obtain a microstructure with grain orientation in a strong magnetic field to improve the performance of the ceramic. When ceramic particles with magnetic anisotropy suspended in a liquid medium are subjected to a magnetic field, the ceramic particles will rotate, and the crystal axis with the maximum antimagnetic susceptibility will be aligned along the direction of the magnetic field. After subsequent sintering, a textured ceramic material can be obtained.

[0047] The technical solution of the present invention has the following advantages:

[0048] The present invention provides a silicon nitride ceramic substrate with high thermal conductivity, high strength, high toughness and uniform color by adjusting the combination of various raw materials in inorganic powder and the amount of each raw material. The substrate is made of α-Si3N4 as the main phase material, β-Si3N4 whiskers doped with a fixed aspect ratio as the first auxiliary phase material, single crystal nano diamond as the second auxiliary phase material, and sintering aids and composite colorants aFe2O3-bCr2O3-cEr2O3-dWO3 are added to prepare a silicon nitride ceramic substrate with high performance, high reliability and stability, which is helpful to promote the industrialization of silicon nitride ceramic substrates. Specifically, the composite colorant in the present invention is composed of transition elements Fe, Cr, and W characterized by an incomplete d shell, and a rare earth element Er characterized by an incomplete f shell. Such ions with incomplete electronic configurations absorb light within a specific range of wavelengths. The environment or coordination field around the transition metal ions of Fe, Cr, and W will affect the absorption characteristics of the ions and thus have a great influence on the color they produce, while the rare earth element Er, which relies on the electron transition in the internal f shell to color, is rarely affected by the environment. The composite colorant aFe2O3-bCr2O3-cEr2O3-dWO3 is dispersed in the silicon nitride matrix material as a single phase pigment particle. This phase is colored and insoluble in the matrix. This pigment is a colored compound that is stable at high temperature and inert in the silicon nitride system. In this stable and chemically inert structure, Fe, Cr, W, and Er ions appear in different valence states and in tetrahedral and octahedral coordination. These characteristics result in strong and stable colors suitable for use as pigments, avoiding the problem of uneven gray coloration near the surface of the sintered silicon nitride ceramic matrix and gray coloration of the body. These pigments provide resistance to glass phase corrosion and increase the adaptability of accepting rare earth ions in solid solution. Single-crystal nanodiamond is distributed in the silicon nitride matrix material as a secondary phase. In the microstructure, it gathers at the grain boundaries. Single-crystal nanodiamond can be densely filled and evenly distributed between silicon nitride particles. Because of its high surface activity and low Debye temperature, it helps to improve the sintering activity of silicon nitride ceramics, increase the driving force during the sintering process, make the structure density of silicon nitride ceramic sintered bodies higher, and improve the mechanical properties of silicon nitride ceramics. For conventional diamonds or micron-sized diamonds, their particle size is much larger than the main phase matrix material, which reduces the density of the microstructure, increases the porosity and hole rate, and causes the mechanical properties to deteriorate. In addition, single-crystal nanodiamond has the dual characteristics of nanomaterials and diamonds, with a more uniform and complete crystal structure and a smaller thermal expansion coefficient, which can ensure uniform and stable chemical and thermodynamic properties. Single-crystal nanodiamond can effectively improve the thermal conductivity of silicon nitride ceramics.

[0049] The silicon nitride ceramic substrate provided by the present invention can form a grain boundary glass phase by limiting the sintering aid, so that the glass phase is combined with the β-Si3N4 grains, and an interwoven structure is formed during the growth of the β needle-shaped grains, thereby making the material have higher strength and fracture toughness.

[0050] The silicon nitride ceramic substrate provided by the present invention can further improve the performance of the material by limiting the parameters of the raw materials.

[0051] The preparation method of the silicon nitride ceramic substrate provided by the present invention adopts tape casting composite constant strong magnetic field forming technology. During the solidification process of the slurry, these antimagnetic ceramic grains will be oriented under the action of the strong magnetic field. The grain orientation is realized in a colloidal medium. The c-axis is arranged in a plane along the tape casting direction, and the a-axis or b-axis of the crystal will be arranged along the direction of the magnetic field, and finally the textured silicon nitride ceramic with a-axis or b-axis orientation is obtained. The strong magnetic field orientation technology can affect the performance of the material by changing the microstructure of the material, that is, the orientation of the grain formation. In the tape casting composite constant strong magnetic field forming technology, the orientation of the grains is carried out in a colloidal medium, there is no requirement for the shape of the grains, and the single ceramic grains are stably dispersed in the slurry and are subjected to a uniform and constant magnetic field force. The process is a continuous operation mode, which is relatively simple and highly operable, with high efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0053] Figure 1 is a microstructure diagram of the tape-cast green body obtained in Example 3 of the present invention;

[0054] Figure 2 3 is a microstructure diagram of the silicon nitride ceramic substrate obtained in Example 3 of the present invention.

[0055] Figure 3 This is a picture of a physical sample of the silicon nitride ceramic substrate obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0056] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0057] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0058] In order to facilitate comparison between data, the parameters of some raw materials selected in the following examples and comparative examples are as follows:

[0059] α-Si3N4 purity>95wt%, particle size distribution D50 is 0.6μm, specific surface area SSA is 11.2m 2 / g, O content is 0.8wt%, and metal impurity contents of Al and Fe are 80ppm respectively;

[0060] The length of β-Si3N4 whiskers is 2 μm, the diameter is 0.4 μm, and the aspect ratio is 7;

[0061] The single crystal nanodiamond is spherical, with a purity of >99.9%, a particle size distribution D50 of 50nm, and a specific surface area SSA of 260m 2 / g;

[0062] The purity of sintering aid is >99.99%, and the particle size distribution D50 is 0.3μm;

[0063] The purity of the composite colorant is >99.99%, and the particle size distribution D50 is 0.4 μm.

[0064] Example 1

[0065] The present embodiment provides a silicon nitride ceramic substrate, in which the main phase material α-Si3N4 accounts for 91% of the inorganic powder composition, the first subphase material β-Si3N4 whisker accounts for 4%, the second subphase material single crystal nanodiamond accounts for 1%, the sintering aid 0.7Gd2O3-0.3MgAl2O4 accounts for 3.2%, and the composite colorant 0.04Fe2O3-0.03Cr2O3-0.1Er2O3 -0.83WO3 accounts for 0.8%.

[0066] The method for preparing the silicon nitride ceramic substrate comprises the following steps:

[0067] The composite colorant and the binary azeotropic mixture solvent (accounting for 20% of the total weight of the inorganic powder, with anhydrous ethanol: acetone = 68wt%: 32wt%) were weighed in proportion and mixed for the first time by vacuum ball milling for 4h, and then α-Si3N4 powder, β-Si3N4 whisker, sintering aid, dispersant (triolein, the same below) and the binary azeotropic mixture solvent (accounting for 70% of the total weight of the inorganic powder) were added in sequence for the second time by vacuum ball milling. The mixture was dispersed for 12 hours, and finally the adhesive (polyvinyl butyral, Sinopharm Reagent Aviation Grade (Shanghai), Sinopharm No. 30153960, the same below) and plasticizer (butyl benzyl phthalate as Class I plasticizer, polyethylene glycol 400 (Sinopharm Reagent CP (Shanghai)) as Class II plasticizer, the same below) were added in turn and vacuum ball milled for 20 hours. The slurry after ball milling was vacuum defoamed at a vacuum degree of 10Kpa for 1 hour to obtain a casting slurry with a viscosity of 17400mPa·s. Among them, the binary azeotropic mixture solvent of anhydrous ethanol and acetone accounted for 90% of the total weight of the inorganic powder, the dispersant accounted for 3% of the total weight of the inorganic powder, the adhesive accounted for 15% of the total weight of the inorganic powder, the Class I plasticizer accounted for 6% of the total weight of the inorganic powder, and the Class II plasticizer accounted for 2% of the total weight of the inorganic powder.

[0068] The scraper height was set to 0.6mm, the film belt travel speed was set to 0.2m / min, and the four-stage drying temperatures were set to 30, 50, 70, and 90℃. The slurry was cast on a casting machine equipped with a constant magnetic field device. The magnetic field strength was 3T, and the magnetic field direction was perpendicular to the casting direction to obtain a 0.3mm thick casting green body. After the green body was cut into Φ150mm by a mold, it was placed in a boron nitride crucible and stacked in 8 layers. The surface of each layer of green body was evenly coated with Si3N4+BN+C (40wt%: 40wt%: 20wt%, the same below) mixed powder. In a flowing N2 atmosphere of 2L / min, the temperature was raised to 250℃ at 0.5℃ / min and kept warm for 4h; then the temperature was raised to 350℃ at 1℃ / min and kept warm for 4h; finally, the temperature was raised to 600℃ at 2℃ / min and kept warm for 6h. After debinding and cooling, the crucible was transferred to a gas pressure sintering furnace, and the temperature was raised to 1400°C at 10°C / min under a N2 pressure of 0.1MPa, and kept warm for 2h; then the N2 pressure was pressurized to 2MPa, the temperature was raised to 1850°C at 6°C / min, and kept warm for 6h; finally, a silicon nitride ceramic substrate sample was prepared.

[0069] Example 2

[0070] This embodiment provides a silicon nitride ceramic substrate, in which the main phase material α-Si3N4 accounts for 91% of the inorganic powder composition, the first subphase material β-Si3N4 whisker accounts for 2%, the second subphase material single crystal nanodiamond accounts for 2%, the sintering aid 0.9Yb2O3-0.1MgAl2O4 accounts for 4.5%, and the composite colorant 0.06Fe2O3-0.05Cr2O3-0.2Er2O3 -0.69WO3 accounts for 0.5%.

[0071] The method for preparing the silicon nitride ceramic substrate comprises the following steps:

[0072] The above-mentioned composite colorant and binary azeotropic mixture solvent (accounting for 20% of the total weight of the inorganic powder) are weighed in proportion and mixed by vacuum ball milling for the first time for 6 hours, and then α-Si3N4 powder, β-Si3N4 whisker, sintering aid, dispersant and binary azeotropic mixture solvent (accounting for 60% of the total weight of the inorganic powder) are added in sequence for the second vacuum ball milling dispersion for 12 hours, and finally adhesive and plasticizer are added in sequence for vacuum ball milling for 20 hours, and the ball-milled slurry is vacuum defoamed for 2 hours at a vacuum degree of 10Kpa to obtain a casting slurry with a viscosity of 20000mPa·s. Among them, the binary azeotropic mixture solvent of anhydrous ethanol and acetone accounts for 80% of the total weight of the inorganic powder, the dispersant accounts for 5% of the total weight of the inorganic powder, the adhesive accounts for 20% of the total weight of the inorganic powder, the type I plasticizer accounts for 7% of the total weight of the inorganic powder, and the type II plasticizer accounts for 4% of the total weight of the inorganic powder.

[0073] The scraper height was set to 0.8mm, the film belt travel speed was set to 0.15m / min, and the four-stage drying temperatures were set to 30, 50, 70, and 90℃. The slurry was cast on a casting machine equipped with a constant magnetic field device. The magnetic field strength was 3T, and the magnetic field direction was perpendicular to the casting direction to obtain a 0.4mm thick casting green body. After the green body was cut into Φ150mm by a mold, it was placed in a boron nitride crucible and stacked in 6 layers. The surface of each layer of green body was evenly coated with Si3N4+BN+C mixed powder. In a flowing N2 atmosphere of 3L / min, the temperature was raised to 250℃ at 0.5℃ / min and kept warm for 8h; then the temperature was raised to 350℃ at 1℃ / min and kept warm for 8h; finally, the temperature was raised to 600℃ at 2℃ / min and kept warm for 8h. After debinding and cooling, the crucible was transferred to a gas pressure sintering furnace, and the temperature was raised to 1500°C at 12°C / min under a N2 pressure of 0.1MPa, and kept warm for 2h; then the N2 pressure was pressurized to 2MPa, the temperature was raised to 1900°C at 4°C / min, and kept warm for 8h; finally, a silicon nitride ceramic substrate sample was prepared.

[0074] Example 3

[0075] The present embodiment provides a silicon nitride ceramic substrate, in which the main phase material α-Si3N4 accounts for 92% of the inorganic powder composition, the first subphase material β-Si3N4 whisker accounts for 3%, the second subphase material single crystal nanodiamond accounts for 1.5%, the sintering aid 0.7Yb2O3-0.3MgAl2O4 accounts for 3%, and the composite colorant 0.06Fe2O3-0.05Cr2O3-0.2Er2O3-0.69WO3 accounts for 0.5%.

[0076] The method for preparing the silicon nitride ceramic substrate comprises the following steps:

[0077] The composite colorant and binary azeotropic mixture solvent (accounting for 20% of the total amount of inorganic powder) are weighed in proportion and mixed by vacuum ball milling for the first time for 6 hours, and then α-Si3N4 powder, β-Si3N4 whisker, sintering aid, dispersant and binary azeotropic mixture solvent (accounting for 60% of the total amount of inorganic powder) are added in sequence for the second vacuum ball milling dispersion for 16 hours, and finally adhesive and plasticizer are added in sequence for vacuum ball milling for 24 hours, and the slurry after ball milling is vacuum defoamed for 2 hours under a vacuum degree of 10Kpa to obtain a casting slurry with a viscosity of 19000mPa·s. The binary azeotropic mixture solvent of anhydrous ethanol and acetone accounts for 80% of the total weight of inorganic powder, the dispersant accounts for 4% of the total weight of inorganic powder, the adhesive accounts for 18% of the total weight of inorganic powder, the type I plasticizer accounts for 8% of the total weight of inorganic powder, and the type II plasticizer accounts for 2% of the total weight of inorganic powder.

[0078] The scraper height was set to 0.7mm, the film belt travel speed was set to 0.25m / min, and the four-stage drying temperatures were set to 30, 50, 70, and 90℃. The slurry was cast on a casting machine equipped with a constant magnetic field device. The magnetic field strength was 3T, and the magnetic field direction was perpendicular to the casting direction. A 0.36mm thick casting green body was obtained. After the green body was cut into Φ150mm by a mold, it was placed in a boron nitride crucible and stacked in 6 layers. The surface of each layer of green body was evenly coated with Si3N4+BN+C mixed powder. In a flowing N2 atmosphere of 1L / min, the temperature was raised to 250℃ at 0.5℃ / min and kept warm for 4h; then the temperature was raised to 350℃ at 1℃ / min and kept warm for 4h; finally, the temperature was raised to 600℃ at 2℃ / min and kept warm for 6h. After debinding and cooling, the crucible was transferred to a gas pressure sintering furnace, and the temperature was raised to 1400°C at 8°C / min under a N2 pressure of 0.1MPa, and kept warm for 1h; then the N2 pressure was pressurized to 2MPa, the temperature was raised to 1900°C at 4°C / min, and kept warm for 12h; finally, a silicon nitride ceramic substrate sample was prepared.

[0079] Figure 1 is the microstructure diagram of the obtained tape-cast green body. Figure 2 is the microstructure diagram of the obtained silicon nitride ceramic substrate. Figure 3This is a physical sample picture of the obtained silicon nitride ceramic substrate. As can be seen from the figure, the tape-cast green body is distributed with large α-Si3N4 particles, small particles of sintering aids and colorants, needle-shaped β-Si3N4 whiskers and smaller nano-diamond particles, and several components are evenly mixed and stacked. The microstructure of the sintered silicon nitride ceramic substrate is densely covered with long columnar β-Si3N4 grains, which are tilted and have obvious orientation, realizing the optimization of thermal conductivity in the direction parallel to the c-axis; the stacking and interweaving of small-diameter long columnar β-Si3N4 grains reduces the size defects produced, so that the material has high strength and fracture toughness. The physical sample of the silicon nitride ceramic substrate is dark gray, with uniform color and no gradual gradient color difference.

[0080] Example 4

[0081] The present embodiment provides a silicon nitride ceramic substrate, in which the main phase material α-Si3N4 accounts for 94% of the inorganic powder composition, the first subphase material β-Si3N4 whisker accounts for 2%, the second subphase material single crystal nanodiamond accounts for 1%, the sintering aid 0.8Yb2O3-0.2MgAl2O4 accounts for 2.5%, and the composite colorant 0.05Fe2O3-0.04Cr2O3-0.15Er2O3 -0.76WO3 accounts for 0.5%.

[0082] The method for preparing the silicon nitride ceramic substrate comprises the following steps:

[0083] The composite colorant and binary azeotropic mixture solvent (accounting for 20% of the total weight of the inorganic powder) are weighed in proportion and mixed by vacuum ball milling for the first time for 6 hours, and then α-Si3N4 powder, β-Si3N4 whisker, sintering aid, dispersant and binary azeotropic mixture solvent (accounting for 80% of the total weight of the inorganic powder) are added in sequence for the second vacuum ball milling dispersion for 16 hours, and finally adhesive and plasticizer are added in sequence for vacuum ball milling for 24 hours, and the ball-milled slurry is vacuum defoamed for 0.5 hours at a vacuum degree of 10Kpa to obtain a casting slurry with a viscosity of 15000mPa·s. The binary azeotropic mixture solvent of anhydrous ethanol and acetone accounts for 100% of the total weight of the inorganic powder, the dispersant accounts for 5% of the total weight of the inorganic powder, the adhesive accounts for 20% of the total weight of the inorganic powder, the type I plasticizer accounts for 8% of the total weight of the inorganic powder, and the type II plasticizer accounts for 2% of the total weight of the inorganic powder.

[0084] The scraper height was set to 0.7mm, the film belt travel speed was set to 0.2m / min, and the four-stage drying temperatures were set to 30, 50, 70, and 90℃. The slurry was tape-cast on a tape-casting machine equipped with a constant magnetic field device. The magnetic field strength was 3T, and the magnetic field direction was perpendicular to the tape-casting direction. A 0.32mm thick tape-cast green body was obtained. After the green body was cut into Φ150mm by a mold, it was placed in a boron nitride crucible and stacked in 8 layers. The surface of each layer of green body was evenly coated with Si3N4+BN+C mixed powder. In a flowing N2 atmosphere of 2L / min, the temperature was raised to 250℃ at 0.5℃ / min and kept warm for 6h; then the temperature was raised to 350℃ at 1℃ / min and kept warm for 6h; finally, the temperature was raised to 600℃ at 2℃ / min and kept warm for 8h. After debinding and cooling, the crucible was transferred to a gas pressure sintering furnace, and the temperature was raised to 1500°C at 8°C / min under a N2 pressure of 0.1MPa, and kept warm for 1h; then the N2 pressure was pressurized to 2MPa, the temperature was raised to 1900°C at 4°C / min, and kept warm for 10h; finally, a silicon nitride ceramic substrate sample was prepared.

[0085] Example 5

[0086] This embodiment provides a silicon nitride ceramic substrate. Compared with the embodiment 3, the only difference is that the magnetic field intensity is 2T.

[0087] Example 6

[0088] This embodiment provides a silicon nitride ceramic substrate. Compared with the embodiment 3, the only difference is that no magnetic field is applied in the tape casting step.

[0089] Comparative Example 1

[0090] This comparative example provides a silicon nitride ceramic substrate. Compared with Example 1, the only difference is that the colorant is different. The colorant 0.35CoO-0.26Cr2O3-0.3Fe2O3-0.09MnO2 of equal mass is used to replace the composite colorant 0.04Fe2O3-0.03Cr2O3-0.1Er2O3-0.83WO3.

[0091] Comparative Example 2

[0092] This comparative example provides a silicon nitride ceramic substrate, which is different from Example 1 only in that diamond with a D50 particle size of 2 μm of equal mass is used instead of single crystal nano-diamond.

[0093] Comparative Example 3

[0094] This comparative example provides a silicon nitride ceramic substrate, in which the main phase material α-Si3N4 accounts for 95% of the inorganic powder composition, the first subphase material β-Si3N4 whisker accounts for 1%, the second subphase material single crystal nanodiamond accounts for 0.6%, the sintering aid 0.7Gd2O3-0.3MgAl2O4 accounts for 2%, and the composite colorant 0.04Fe2O3-0.03Cr2O3-0.1Er2O3 -0.83WO3 accounts for 1.4%.

[0095] Test Case

[0096] The silicon nitride ceramic substrates obtained in each embodiment and comparative example were subjected to performance tests, and the specific test methods are as follows:

[0097] Density: GB / T 25995-2010 Test method for density and apparent porosity of fine ceramics;

[0098] Bending strength: GB / T 6569-2006 Test method for bending strength of fine ceramics;

[0099] Thermal conductivity: GB / T 22588-2008 flash method for measuring thermal diffusivity or thermal conductivity;

[0100] Volume resistivity: GB / T 31838.22019 Dielectric and resistive properties of solid insulating materials Part 2: Resistive properties (DC method) Volume resistance and volume resistivity;

[0101] Breakdown voltage: GB / T 5593-2015 Structural ceramic materials for electronic components;

[0102] Fracture toughness: GB / T 23806-2009 Test method for fracture toughness of fine ceramics, single edge pre-cracked beam (SEPB) method;

[0103] Color difference: GB / T 3979-2008 Measurement method of object color.

[0104] The specific test results are shown in the table below:

[0105] Table 1

[0106]

[0107] From the data in the above table, it can be seen that compared with Example 6 without adding a magnetic field, Examples 1-5 apply a magnetic field during the tape-casting process, which can effectively improve the thermal conductivity of the silicon nitride ceramic substrate. This shows that the ceramic particles with magnetic anisotropy suspended in the liquid medium are affected by the magnetic field, and the crystal axis with the maximum anti-magnetic susceptibility will be arranged along the direction of the magnetic field, and a ceramic material with texture is obtained after later sintering. In addition, within the appropriate magnetic field strength range, as the magnetic field strength increases from 2T (Example 5) to 3T (Example 3), the thermal conductivity and bending strength of the silicon nitride ceramic substrate are improved, which shows that increasing the magnetic field strength helps to improve the orientation of the grains. The conventional colorant used in Comparative Example 1 has a significantly increased color difference compared with the examples. This is because it is not resistant to high temperatures and has a weak ability to resist reducing atmospheres. It is partially decomposed during the high-temperature sintering process of silicon nitride ceramics, resulting in large color differences in the sintered ceramics and poor color uniformity. Comparative Example 2 uses micron-sized diamond particles instead of single-crystal nanodiamonds, and its flexural strength and thermal conductivity both show a significant decrease. This is because the sintering activity of micron-sized diamonds is low, and they are distributed in the form of large particles at the junction of silicon nitride grains, which hinders the efficiency of thermal conduction. In Comparative Example 3, the amount of sintering agent added is too little, resulting in loose sintering and deterioration of mechanical properties; and the amount of colorant added is too much. Although it reduces the color difference of silicon nitride ceramics and improves color uniformity, too much colorant will hinder the efficiency of thermal conduction and reduce the insulation performance of silicon nitride after sintering. In summary, each functional component needs to be controlled within an appropriate range, so as to effectively improve the mechanical, thermal and electrical properties and color uniformity and stability of the silicon nitride ceramic substrate.

[0108] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A silicon nitride ceramic substrate, characterized in that: Prepared from inorganic powder, based on the total mass of the inorganic powder, it includes the following components in percentage by mass: α-Si3N4 accounts for 91% to 94%; β-Si3N4 whiskers account for 2% to 4%; Single crystal nanodiamond accounts for 1% to 2%; The proportion of sintering aids is 2.5% to 4.5%; The proportion of composite colorants is 0.5% to 0.8%; The composition of the composite colorant is aFe2O3-bCr2O3-cEr2O3-dWO3, and a:b:c:d=(0.04-0.06):(0.03-0.05):(0.1-0.2):(0.69-0.83); The method for preparing the silicon nitride ceramic substrate comprises the following steps: S1, preparing inorganic powder into casting slurry; S2, casting the obtained casting slurry in the presence of a magnetic field to obtain a casting green body, wherein the direction of the magnetic field is perpendicular to the casting direction; S3, debinding and sintering the obtained tape-cast green body to obtain the silicon nitride ceramic substrate; wherein, before the debinding step, the tape-cast green body is stacked and mixed powder is sprayed between the layers, wherein the mixed powder comprises Si3N4:BN:C=(35-45)wt%:(35-45)wt%:(10-30)wt%.

2. The silicon nitride ceramic substrate according to claim 1, characterized in that: The composition of the sintering aid is xRE2O3-(1-x)MgAl2O4, wherein 0.7≤x≤0.9, and RE is a lanthanide rare earth element.

3. The silicon nitride ceramic substrate according to claim 2, characterized in that: RE includes at least one of the elements La, Ce, Nd, Gd, and Yb.

4. The silicon nitride ceramic substrate according to any one of claims 1 to 3, characterized in that: Satisfy at least one of the following (1)-(5): (1) α-Si3N4 purity>95wt%, particle size distribution D50 is 0.6~0.8μm, specific surface area SSA is 10~13m 2 / g, O content ≤ 0.8wt%, metal impurity content Al < 100ppm, Fe < 100ppm; (2) The length of β-Si3N4 whiskers is 2 to 3 μm, the diameter is 0.3 to 0.4 μm, and the aspect ratio is 6 to 12; (3) Single crystal nanodiamond is spherical or quasi-spherical, with a purity of >99.9%, a particle size distribution D50 of 40-50 nm, and a specific surface area SSA of 260-300 m 2 / g; (4) The purity of sintering aid is >99.99%, and the particle size distribution D50 is 0.2-0.4 μm; (5) The purity of the composite colorant is >99.99%, and the particle size distribution D50 is 0.2-0.4 μm.

5. A method for preparing a silicon nitride ceramic substrate according to any one of claims 1 to 4, characterized in that: The steps include: S1, preparing inorganic powder into casting slurry; S2, casting the obtained casting slurry in the presence of a magnetic field to obtain a casting green body, wherein the direction of the magnetic field is perpendicular to the casting direction; S3, debinding and sintering the obtained tape-cast green body to obtain the silicon nitride ceramic substrate.

6. The method for preparing a silicon nitride ceramic substrate according to claim 5, characterized in that: In step S2, the magnetic field strength is 2T to 4T.

7. The method for preparing a silicon nitride ceramic substrate according to claim 5 or 6, characterized in that: In step S1, the casting slurry also includes a dispersant, a binder and a plasticizer; And / or, the viscosity of the casting slurry is 15000-20000 mPa·s.

8. The method for preparing a silicon nitride ceramic substrate according to claim 5 or 6, characterized in that: In step S2, during the tape casting process, the scraper height is set to 0.5-0.8 mm, the tape casting speed is set to 0.15-0.25 m / min, the drying temperature is set to 30-90° C., and the green body thickness is set to 0.2-0.4 mm; And / or, the diameter of the green body is Φ120-180 mm.

9. The method for preparing a silicon nitride ceramic substrate according to claim 5 or 6, characterized in that: In step S3, the debinding step includes heating the tape-cast green body to 250-270°C at 0.5-0.8°C / min under a protective atmosphere, and keeping the temperature for 4-8 hours; then heating the green body to 320-350°C at 1-2°C / min, and keeping the temperature for 4-8 hours; then heating the green body to 580-620°C at 2-3°C / min, and keeping the temperature for 6-8 hours; And / or, in step S3, before the debinding step, the tape-cast green body is stacked and mixed powder is sprayed between the layers, in which Si3N4:BN:C=(35-45)wt%:(35-45)wt%:(10-30)wt%.

10. The method for preparing a silicon nitride ceramic substrate according to claim 5 or 6, characterized in that: In step S3, the sintering step includes heating to 1400-1500°C at 8-12°C / min under a N2 pressure of 0.1-0.3MPa, and keeping warm for 1-2h; then pressurizing to a N2 pressure of 2-3MPa, heating to 1850-1900°C at 4-6°C / min, and keeping warm for 6-12h.

11. Use of the silicon nitride ceramic substrate according to any one of claims 1 to 4 or the silicon nitride ceramic substrate prepared by the preparation method according to any one of claims 5 to 10 in the field of electronic packaging.

Citation Information

Patent Citations

  • Colorful ceramic and preparing method thereof

    CN105622169A

  • Low-temperature sintering process of aluminum nitride ceramic material

    CN116425551A

  • Method of producing ceramic and ceramic substrate produced by using the same

    JP2002121076A